Absorption and metabolism of fructose and its relationship with human health - CAI Wenwen; LI Duo (浙江大学学报. 农业与生命科学版)
Fructose is a monosaccharide, which is greatly sweeter than glucose and sucrose. In recent years, high fructose corn syrup has been widely used in beverages and food industry globally. However, the effect of fructose on human health has received much attention in current years. In this review, we mainly discussed the food source, absorption and metabolism of fructose, relationship between fructose and metabolic disorders, and recommendation intake of total sugar.Crystalline fructose is dried, ground, and highly pure. Fructose is found in most fruits and vegetables either as a monosaccharide or as a unit of sucrose. The ratio of fructose to glucose in most natural food is approximately 1∶1. Fructose has the lowest glycemic index of all natural sugars. High-fructose corn syrup (HFCS) is a mixture of fructose and glucose, which is widely used in food industry, added into soft drinks and baked foods for its palatability and good taste. HFCS-42, HFCS-55 and HFCS-90 are three kinds of HFCS, and the number for each HFCS represents the percentage of fructose in the syrup. Free fructose is absorbed directly by intestine via facilitated transport involving GULT5 transport proteins. Unabsorbed fructose in intestine can cause abdominal symptoms such as diarrhea and abdominal pain. When fructose exists in a 1∶1 ratio with glucose, it can be absorbed mostly. Unlike glucose, fructose can be metabolized in liver, where it can be partially converted into glucose, and mostly metabolized to fatty acid, and the latter can be synthesized into triacylglycerol. Fructose is firstly metabolized into fructose 1-phosphate by fructose to kinase referred to as fructolysis. Unlike glycolysis, in fructolysis the triose glyceraldehyde lacks a phosphate group. Fructose 1-phosphate then is hydrolyzed by aldose B to form dihydroxy acetone phosphate and glyceraldehyde. DHAP can either be isomerized to glyceraldehyde 3-phosphate by triosephosphate isomersae or reduced to glycerol 3-phosphate by glycerol 3-phosphate dehydrogenase. The glyceraldehyde produced may also be converted to glyceraldehyde 3-phosphate by glyceraldehyde kinase or further converted to glycerol 3-phosphate by glycerol 3-phosphate dehydrogenase. The metabolism of fructose yields intermediates in the gluconeogenic pathway leading to glycogen synthesis as well as fatty acid and triglyceride synthesis. Triacylglycerol can be accumulated in liver to cause non-alcohol fatty liver and insulin resistance in liver. Triglycerides are incorporated into very-low-density lipoproteins, which are released from the liver destined toward peripheral tissues for storage in both fat and muscle cells. Then, triacylglycerol can also be transported to other organs and tissues to increase the risk of insulin resistance, obesity and cardiovascular disease.Based on the available evidence, WHO recommends a reduced intake of free sugars throughout the life to limit free sugars intake to less than 10% of total energy intake. WHO suggests a further reduction of the intake of free sugars to below 5% of total energy intake.In conclusion, there exits a relationship between fructose and non-alcohol fatty liver, obesity, cardiovascular disease and insulin resistance. Therefore, fructose should be applied in an appropriate way or it will exert a detrimental influence on health. It is reasonable to pay more attention on reducing fructose intake.